2022
DOI: 10.1002/ael2.20076
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative comparison of the storage protein distribution in glandless and glanded cottonseeds

Abstract: Glanded (Gd) cottonseed (Gossypium hirsutum L.) contains scattered gossypol glands. Glandless (Gl) cottonseed is a new type of seed containing only trace levels of gossypol. This work quantitatively compared the content and migration pattern of Gd and Gl protein isolates. Both protein samples were subjected to sodium dodecyl sulfate (SDS)-gel electrophoresis, and the protein gel bands were separated into seven partitions for peptide mass spectroscopic analysis. While multiple peptide fragments (isoformers) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
(30 reference statements)
1
9
0
Order By: Relevance
“…The seed protein level was stable, and the seed protein content in the transgenic lines was like the non-transgenic control ( Table 1 ). Though, He et al (2022) observed that storage protein was affected by gossypol because that gossypol interacts with the free epsilon-amino groups from lysine and arginine likely promoting the formation of protein aggregates, which make not only the protein hard to extract. So, the distribution pattern and abundance of the storage proteins in the transgenic cottonseeds need to be investigated in future research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The seed protein level was stable, and the seed protein content in the transgenic lines was like the non-transgenic control ( Table 1 ). Though, He et al (2022) observed that storage protein was affected by gossypol because that gossypol interacts with the free epsilon-amino groups from lysine and arginine likely promoting the formation of protein aggregates, which make not only the protein hard to extract. So, the distribution pattern and abundance of the storage proteins in the transgenic cottonseeds need to be investigated in future research.…”
Section: Resultsmentioning
confidence: 99%
“…Cottonseed protein contains a balanced proportion of necessary amino acids and have been widely applied as food additives rich in nutrients ( Zhuge et al, 1988 ) and other added-value products such as coating, adhensives, bioplastics and films, antioxidant fraction etc. ( He et al, 2022 ). As we all know, the presence of toxic gossypol greatly limited cottonseed’s utilization especially for cottonseed protein and meal.…”
Section: Discussionmentioning
confidence: 99%
“…While a recent in silico analysis suggest the potential for cottonseed derived protein to be allergenic is low [ 24 ], the data presented here indicate care should be taken utilizing cottonseed protein as human food. Several other conserved plant allergens can be found in cottonseed including 2 S albumins, vicilin-like antimicrobial peptides 2-1/2, phosphoglycerate kinase, and protein disulfide-isomerase [ 4 , 5 , 20 , 33 , 35 , 36 , 37 ]. In peanuts and tree nuts, the 2 S albumin proteins are potent allergens [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The small 2 S albumin proteins belong to the prolamin superfamily, contain a conserved set of cysteine residues, and are commonly cleaved into two subunits [ 18 , 19 ]. These three conserved proteins (legumins, vicilins, and 2 S albumins) have been identified in both Gd and Gl protein preparations [ 4 , 5 ], although the pattern of their distribution is not the same [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is either glanded or glandless depending on its seed with or without gossypol glands ( Figure 1 A) [ 1 , 2 ]. Cottonseed contains many bioactive molecules including gossypol ( Figure 1 B), quercetin, gallic acid, 3,4-dihydroxybenzoic acid, flavonoids, cyclopropenoid fatty acids, and peptides [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Most of these value-added products possess health promotion and disease prevention potentials [ 6 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%